Overview of 5G multi-channel redundant transmission technology - MA Shuai; YANG Bohan; YANG Fengbo; WEI Anni; ZHENG Chenglong (Dianxin kexue)
At present, the society is in an era of rapid development of science and technology, and the rapid development of wireless communication technology has not only promoted the digital transformation of industry, transportation, medical and other fields, but also continuously upgraded wireless communication networks, trying to move from wired to wireless. With the continuous evolution of computer technology and wireless communication technology, many application scenarios require highly reliable transmission in a wireless environment. Especially in the fields of modern industrial automation and autonomous driving, the demand for highly reliable transmission is more urgent. 5G technology was delved into, which was one of the most advanced wireless transmission technologies in the industry, focusing on multi-channel redundant transmission technology within 5G systems. The key points of the technology in terms of application background, technical principles and technical route were summarized. In terms of application background, the practical application requirements of 5G redundant transmission in wireless scenarios such as modern industrial automation and autonomous driving were highlighted. In terms of technical principles, the relevant research was summarized and sorted out from the end-to-end multi-channel redundant transmission of services, the analysis of the technical principles of 5G multi-channel redundant transmission were focused on, and its unique advantages in improving transmission reliability were explained. In terms of technical routes, the development direction of 5G multi-channel redundant transmission technology and various possible implementation paths were comprehensively considered. Finally, the difficulties and challenges of the future development of 5G multi-channel redundant transmission technology were pointed out, and its future development trend was discussed, so as to better understand the key role and prospect of 5G redundant transmission technology in the field of wireless communication.